CORRELATION BETWEEN STUDENTS READING HABIT AND THEIR READING COMPREHENSION SKILL AT HEALTH SCIENCES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Reading is a complex process of decoding symbols to construct or derive meaning. Reading is a good activity to increase knowledge and experiences. People can get much information, idea, and also opinion by reading. The method used in this research is quantitative correlational study. The data of 80 students were collected through a simple random sampling technique. Questionnaires and tests were used as the instruments of this research. The researcher took the online data by Google form. Reading habit questionnaires were given first to the students. This test aims to know the students reading habit score. Second, reading comprehension tests was conducted to measure students reading comprehension skill. Based on the results obtained the average level of the reading habits and reading comprehension of students is high, with an average score of 97.86 for reading habit and 71.90 for reading comprehension. Then the researchers analyzed the correlation using Pearsons Product Moment Formula to correlate both reading habit (Variable X) and reading comprehension (Variable Y). The result showed that the r-value is 0.924 and the r-table is 0.220. It means that the r-value is higher than the r-table and Ha is accepted and Ho is rejected. It can be concluded that there was a strong and very high correlation between students reading habit and their reading comprehension skills at Health Sciences Faculty, Kadiri University.